A comparative analysis on the import and export trade patterns of China's mechanical and electrical products. Issue 1 (July 2021) - Hong, Yu; Qu, Bingbing; Wang, Yuan; Liu, Ting
Abstract: This study uses annual data from 1985 to 2019 to analyze the export and import trade patterns of mechanical and electrical products of China. We employ H-index, or the difference between net export capability and symmetric revealed comparative advantage, to assess the trade policies in exports and imports. The results reveal that China has comparative advantage in the imports, and has had comparative disadvantage in the exports before 1999. In recent years, the policy of trade protectionism has been adopted, which promotes exports in terms of exports and restricts imports in terms of imports.